(untitled) (Research, Society and Development, 2023)
In contemporary times, the presence of digital technologies is observed in practically all sectors of society, and these technologies have become part of daily education, a necessity in human relationships and in the teaching and learning process. The objective of this study was to analyze the perception of teachers at Colégio Militar da Polícia Militar II in Manaus about the use of Digital Information and Communication Technologies (ICTs), as a possibility of insertion in the teaching and learning process in Science. A mixed descriptive-exploratory and cross-sectional study. The population consisted of six Science teachers, from Elementary School II of the aforementioned institution. Questionnaires were applied to survey the sociodemographic profile of the participants and to diagnose the use of ICTs in pedagogical practice. The data obtained were analyzed by descriptive statistics and by content analysis, based on Bardin. The teachers’ perceptions were that the most used ICTs are data show, computer and sound box; although some assess the use of ICTs as reasonable, most do not perceive it, reporting, among others, lack of structure and lack of incentive; passing images and videos is what contributes most in teaching practice, improving visual learning; with the use of ICTs, students show more interest and better understand the content, improving its assimilation; among the challenges presented for the implementation of technologies in the classroom, the most significant were structural problems, lack of technical support and equipment that does not work, characterizing lack of structure, lack of internet and non-availability of resources; teachers are willing to learn different digital technologies, to facilitate content, improve the teaching and learning process and for practicality, emphasizing programming; not all of them use ICTs, or use them sporadically or insufficiently. It is concluded that teachers consider the insertion of ICTs important, but there are obstacles that need to be overcome.